Neutrophil function in pregnancy and rheumatoid arthritis. Issue 7 (1st July 2000) - Crocker, I P; Baker, P N; Fletcher, J
Abstract : BACKGROUND: Pregnancy exerts suppressive effects on rheumatoid arthritis (RA). An attenuation in neutrophil function in late pregnancy which may explain this amelioration has previously been reported. OBJECTIVE: A longitudinal investigation of neutrophil activity in healthy pregnant women (n=9) and pregnant patients with RA (n=9), compared with age matched non-pregnant patients with RA (n=12) and healthy controls (n=22). METHODS: Neutrophil activation was measured in response to the physiological receptor agonists, n-formyl-methionyl-leucyl-phenylalanine (fMLP) and zymosan activated serum (ZAS). Superoxide anion production (respiratory burst) was determined by lucigenin enhanced chemiluminescence (LUCL); secondary granule lactoferrin release by enzyme linked immunosorbent assay (ELISA); and CD11b, CD18, and CD62L expression by flow cytometric analysis. RESULTS: Stimulated neutrophil LUCL was significantly reduced in both pregnant women with RA and healthy pregnant women in the second (fMLP 43% and 69%, ZAS 43% and 59%, respectively) and third trimesters (fMLP 24% and 44%, ZAS 32% and 38%, respectively). Responses returned to normal within eight weeks of delivery and unstimulated levels remained unchanged throughout pregnancy. Basal and stimulated CD11b, CD18, and CD62L expression showed no variations throughout gestation for both pregnancy groups. Likewise, stimulated lactoferrin release and plasma lactoferrin remained unchanged. Certain morphological differences in RA neutrophils were highlighted by the flow cytometric analysis. Moreover, resting neutrophils and stimulated cells from patients with RA, including pregnant subjects, showed a marked increase in LUCL, but a reduction in CD11b, CD18, and CD62L. Low dose prednisolone and methylprednisolone had no effect on neutrophil parameters over the period of treatment with non-steroidal anti-inflammatory drugs. CONCLUSION: The attenuation to neutrophil respiratory burst in both healthy and RA pregnancies may offer an explanation for the pregnancy induced remission of this inflammatory disorder.